Finding Love in The Pages of The Newspaper: An Analysis of The Kompas Contact Column in 1997 - Mokoginta, Fatimah; Rochwulaningsih, Yety; Puguh, Dhanang Respati (Publikasi Berkala Pendidikan Ilmu Sosial, 2026)
The "Contact" column is a matchmaking agency through classified ads published in the Kompas daily since 1978. The existence of this column reveals that print media plays a role in shaping social interaction patterns and the representation of cultural values during the transition to modernity. This article uses historical methods by exploring this column to reveal how individuals display their identities, construct ideal partner images, and negotiate traditional and modern values. The analysis shows that although the "Contact" column offers a modern medium that allows for a more open matchmaking process, traditional values such as religious beliefs and ethnicity remain important elements in determining potential partners. At the same time, new criteria have emerged, such as education level, occupation, and economic status, which are influenced by educational quality. This study confirms that the practice of matchmaking through print media is a form of adaptation of tradition within a modern framework.